Part I: Synthesis of sex pheromone of the pine sawfly, Macrodiprion Nemoralis. Part II: Synthetic studies towards the total synthesis of iriomoteolide-1a - Chin, Yen Jin (2011)
Conjugate addition of Grignard reagents to α,β-unsaturated esters is one of the most convergent strategies for the construction of C–C bonds. Our group has previously developed a highly efficient CuI-Tol-BINAP-catalyzed asymmetric conjugate using Grignard reagents. The absolute stereochemistry of the newly introduced alkyl group can easily be controlled by using the enantiomer of the ligand. Therefore, one of the highlights in this thesis is to demonstrate the versatility of our group’s asymmetric conjugate addition for synthesis of natural products. In the first part of this thesis, an elegant display of the CuI-Tol-BINAP-catalyzed asymmetric conjugate addition is established in the total synthesis of sex pheromone of the pine sawfly, Macrodiprion Nemoralis (SRRS-1). The key features of our strategy are: (I) one-pot DIBAL-H reduction–Wittig olefination, (II) olefin cross metathesis of fragment A and fragment B, and (III) a CuI-Tol-BINAP-catalyzed asymmetric conjugate addition using Grignard reagents in good yields and excellent stereoselectivities. In the final part of this thesis, the key fragment of a diasteoremer of iriomoteolide-1a (136) was synthesized via a convergent synthetic strategy that featured the use of our group’s asymmetric conjugate addition and Paterson aldol. The synthesis also demonstrated a successful intermolecular Yamaguchi esterification between two elaborate molecular fragments. As excellent enantio- and distereo-control was achieved during the synthesis, a single isomer was isolated towards the end of the synthesis.